Hypolimnetic deoxygenation enhanced production and export of recalcitrant dissolved organic matter in a large stratified reservoir. (1st July 2022) - Qu, Liyin; He, Chen; Wu, Zetao; Dahlgren, Randy A.; Ren, Mingxing; Li, Penghui; Shi, Quan; Li, Yan; Chen, Nengwang; Guo, Weidong
Highlights: DOM sources and transformations were investigated along a river-reservoir continuum. Deoxygenation enhanced hypolimnetic refractory DOM production and lateral export. Inland dark waters are hotspots for microbial carbon transformation and turnover. Abstract: Global impoundment of river systems represents a major anthropogenic forcing to carbon cycling in reservoirs with seasonal thermal stratification. Currently, a quantitative and mechanistic understanding of how hypolimnetic deoxygenation in stratified reservoirs alters dissolved organic matter (DOM) cycling and lateral transport along the river continuum remains unresolved. Herein, we used optical and high-resolution mass spectrometric analyses to track seasonal and spatial compositional changes of DOM from a large, subtropical impounded river in southeast China. Aliphatic compounds were contributed by algal blooms to epilimnetic DOM during the spring/summer and by baseflow to the overall DOM pool during low-discharge periods. Deoxygenation-driven hypolimnetic mineralization enhanced in situ production of bio-refractory molecules and humic-like fluorescent DOM (FDOMH ) by utilizing bio-labile DOM and settling biogenic particles during periods of stratification. Production efficiency of hypolimnetic FDOMH was 159–444% higher than that of the global dark ocean, and was strongly regulated by temperature and possibly substrate supply. The in situ production rate of hypolimnetic FDOMH was four to five orders-of-magnitude higher than the dark ocean, with much faster turnover rates in dark inland waters versus the dark ocean. Collectively, these findings indicate that the hypolimnion is a hotspot for microbial carbon transformations, and hence an important source and pool of refractory DOM in aquatic systems. The lateral FDOMH flux increased 10.8–32.1% due to hypolimnetic reservoir release during periods of stratification, highlighting the importance of incorporating hypolimnetic carbon transformations into models for carbon cycling of inland waters and the land-sea interface. Graphical abstract: Image, graphical abstract